Effect of fertilizer treatments on jute (Chorchorus olitorius), microbial dynamics in its rhizosphere and residual fertility status of soil - MAJUMDAR, B; SAHA, A R; GHORAI, A K; SARKAR, S K; CHOWDHURY, H; KUNDU, D K; MAHAPATRA, B S (The Indian Journal of Agricultural Sciences, 2014)
The effect of various fertilizer treatments on jute (Corchorus olitorius) and their residual effect on soil fertility along with the microbial dynamics in jute rhizosphere were studied during 2008-11. Application of recommended dose of fertilizer (100 % NPK) was sufficient for jute fibre yield while nutrient uptake was significantly higher with 150% NPK but at par only with 100% NPK + 10 tonnes FYM/ha when N and P are considered. The population of beneficial microbes and enzymatic activities, viz. dehydrogenase, urease, fluorescein diacetate hydrolyzing activity, acid and alkaline phosphatase in jute rhizosphere after 60 days of sowing were significantly higher with 100% NPK + 10 tonnes FYM/ha over all treatments including 100 and 150% NPK. The soil microbial biomass carbon and basal soil respiration rate in jute rhizosphere followed the same trend as that of enzyme activities. There was build up of residual soil fertility after three years in all the treatments except control and 50% NPK compared to initial status and the application of 100% NPK with 10 tonnes FYM/ha helped in higher residual status of organic carbon, available N, P and K in soil. Integration of recommended dose of fertilizer with 10 tonnes FYM/ha proved to be the best possible option for sustainable jute fibre production and maintenance of soil microbial health and fertility status.